Financial performance analysis of effect of disclosure of corporate social responsibility (corporate social responsibility) study of commercial Bank of Indonesia in the year 2010-2012 - Fadli, David; ', Hardi; ', Nurazlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
CSR (Corporate Social Responsibility) is one of the obligations to be undertaken by the company in accordance with the content of article 74 of UU no. 40 of 2007 on Limited Liability Companies, social responsibility, and the environment applicable to the company who manage / own impact on natural resources and unrestricted contributions and included in the financial statements. This study aims to determine empirically the effect of size and the disclosure of corporate social responsibility. To determine empirically the effect and profitability of the corporate social responsibility disclosure. To determine empirically the influence and leverage on the disclosure of corporate social responsibility. all domestic banks in Indonesia, which operates the period 2011-2012, amounting to as many as 21 companies. Hypothesis testing is performed using the t test, using multiple linear regression analysis model. Based on the results of the t test to know that the financial performance consisting of the ratio of Size, Profitability, Leverage and simultaneously affect the banking CSR in Indonesian at 2011-2012. Partially affect the financial performance of CSR and Leverage Size is variable. While the profitability variable partial effect on the banking CSR in Indonesian at 2011-2012. Ratio has dominant influence in affecting CSR is the variable Leverage Size.Keywords: Size, Profitability, Leverage, Disclosure of Corporate Social Responsibility